2013
DOI: 10.1128/aem.03095-12
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Vibrio vulnificus into Marine Aggregates and Its Subsequent Uptake by Crassostrea virginica Oysters

Abstract: Marine aggregates are naturally forming conglomerations of larvacean houses, phytoplankton, microbes, and inorganics adhered together by exocellular polymers. In this study, we show in vitro that the bacterial pathogen Vibrio vulnificus can be concentrated into laboratory-generated aggregates from surrounding water. We further show that environmental (E-genotype) strains exhibit significantly more integration into these aggregates than clinical (C-genotype) strains. Experiments where marine aggregates with att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 31 publications
6
58
0
1
Order By: Relevance
“…This exposure to anaerobiosis in the environment, and the prevalence of E-genotypes in oysters as well as the water column, may result in the differences between Cand E-genotype numbers of V. vulnificus (74). Our lab has previously shown an innate difference in expression levels of type IV pili aerobically (54), and these results further validate those findings as well as expound upon this under conditions lacking oxygen.…”
Section: Figsupporting
confidence: 76%
“…This exposure to anaerobiosis in the environment, and the prevalence of E-genotypes in oysters as well as the water column, may result in the differences between Cand E-genotype numbers of V. vulnificus (74). Our lab has previously shown an innate difference in expression levels of type IV pili aerobically (54), and these results further validate those findings as well as expound upon this under conditions lacking oxygen.…”
Section: Figsupporting
confidence: 76%
“…Tamplin et al 1990, Neogi et al 2012. However, in some recent studies both free-living lifestyles or communities associated with aggregates have been reported for Vibrio (Lyons et al 2007, Froelich et al 2013, Szabo et al 2013. A second hypothesis of our study is therefore that Vibrio is found more in particles than free-living in plankton.…”
Section: Introductionmentioning
confidence: 45%
“…Vibrios have been detected on a large variety of biological surfaces, especially animals (Thompson et al 2004, Baffone et al 2006, Main et al 2015, and are also associated with various types of organic particles of non-animal origin (Lyons et al 2007, Froelich et al 2013. Recently, there has been evidence that vibrios can remain free-living (Mourino-Perez et al 2003, Worden et al 2006, Eiler et al 2006, although little is known on the factors determining whether they remain free-living versus particle-attached (Takemura et al 2014).…”
Section: Are Vibrios Found Preferentially Attached To Particles?mentioning
confidence: 99%
“…10%). We recently reported that if V. vulnificus cells are allowed to incorporate into marine aggregates ("snow") and then added to oyster tank water, the efficiency of uptake is greatly increased, and C-/E-genotype differences are seen (77).…”
Section: Association Of V Vulnificus With Oystersmentioning
confidence: 99%